Population dynamics, ethnic relations and trade among javanese transmigrants in east kalimantan - Evers, Hans-Dieter; Clauss, Wolfgang ; Gerbe, Solvay (Population Studies Center Gadjah Mada University, 1988)
36 hlm.: ilus.; 23 cm